Menacing Environments Ecohorror in Contemporary Nordic Cinema - Bigelow, Benjamin A. (New Directions in Scandinavian Studies, 2023)
Known for their progressive environmental policies and nature-loving citizens, Nordic countries also produce what may seem a counterintuitive film genre: ecohorror, where distinctions between humans and nature are blurred in unsettling ways. From slashers to arthouse thrillers, transnational Nordic ecohorror films such as Antichrist (dir. Lars von Trier, 2009) and Midsommar (dir. Ari Aster, 2019) have garnered commercial and critical attention, revealing an undercurrent of ecophobia in Nordic culture that belies the region's reputation for environmental friendliness. In Menacing Environments, Benjamin Bigelow examines how ecohorror rings some of the same alarm bells that climate activists have sounded, suggesting that the proper response to the ongoing climate catastrophe is not optimism and a market-friendly focus on sustainable development, but rather fear and dread. Bigelow argues that ecohorror destabilizes the two pillars of Nordic society-the autonomous individual and the sovereign state. He illustrates how doing away with any clean separation of the domains of human culture from a wild, untamed realm of nature reminds viewers of the complex and often threatening material entanglements between humans and their environments. Through Bigelow's analysis, ecohorror proves to be a potent vehicle not only for generating a strong affective response in audiences but also for taking on the revered institutions, unquestioned ideological orthodoxies, and claims of cultural exceptionalism in contemporary Nordic societies. Menacing Environments is freely available in an open access edition thanks to TOME (Toward an Open Monograph Ecosystem) and the generous support of the University of Minnesota.